BOND AS A SAFE HAVEN DURING MARKET CRASH: EXAMINATION OF COVID-19 PANDEMIC IN ASEAN-5 - Gabriela Elvina Dwiastuti Siahaan; Robiyanto Robiyanto (Jurnal Manajemen dan Kewirausahaan, 2021)
The central aim of this paper is to examine the effectiveness of corporate bonds and government bonds against the stock price fluctuation in ASEAN-5 countries (Indonesia, Malaysia, Philippines, Thailand and Singapore). Highlighting an important event of COVID-19, we investigate whether bonds provide protection by utilizing Q-REG method. The noteworthy finding is that bonds consistently act as a hedge for Malaysia and Philippines, while regarded as a diversifier for Indonesia’s capital market. However, this study observed that corporate bonds successfully become a strong safe haven for Thailand and Singapore capital market. Similar result was also found for Singapore government bonds which provides a valuable return during the pandemic of COVID-19.